Beyond benevolence : the New York Charity Organization Society and the transformation of American social welfare, 1882-1935 - Greeley, Dawn M. (Philanthropic and nonprofit studies, 2022)
"A comprehensive history of one of the largest charitable organizations in early modern America. Drawing on extensive archival records, Beyond Benevolence tells the fascinating story of the New York Charity Organization Society. The period between 1880 and 1935 marked a seminal, heavily debated change in American social welfare and philanthropy. The New York Charity Organization Society was at the center of these changes and played a key role in helping to reshape the philanthropic landscape. Greeley uncovers rarely seen letters written to wealthy donors by working-class people, along with letters from donors and case entries. These letters reveal the myriad complex relationships, power struggles, and shifting alliances that developed among donors, clients, and charity workers over decades as they negotiated the meaning of charity, the basis of entitlement, and the extent of the obligation between classes in New York. Meticulously researched and uniquely focused on the day-to-day practice of scientific charity as much as its theory, Beyond Benevolence offers a powerful glimpse into how the trajectory of one charitable organization reflected a nation's momentous social, economic, and political upheavals as it moved into the 20th century"--